Single-event multilevel surgery, but not botulinum toxin injections normalize joint loading in cerebral palsy patients. (June 2020) - Van Rossom, S.; Kainz, H.; Wesseling, M.; Papageorgiou, E.; De Groote, F.; Van Campenhout, A.; Molenaers, G.; Desloovere, K.; Jonkers, I.
Abstract: Background: Many patients with cerebral palsy present a pathologic gait pattern, which presumably induces aberrant musculoskeletal loading that interferes with natural bone growth, causing bone deformations on the long term. Botulinum toxin interventions and single-event multilevel surgeries are used to restore the gait pattern, assuming that a normal gait pattern restores musculoskeletal loading and thus prevents further bone deformation. However, it is unknown if these interventions are able to restore musculoskeletal loading. Hence, we investigated the impact of botulinum toxin injections and single-event multilevel surgery on musculoskeletal loading. Methods: Gait data collected in 93 children with bilateral cerebral palsy, which included pre- and post multi-level botulinum toxin (49 children) and single-event multilevel surgery (44 children) assessments, and 15 typically developing children were retrospectively processed using a musculoskeletal modelling workflow to calculate joint angles, moments, muscle and joint contact force magnitudes and orientations. Differences from the typically developing waveform were expressed by a root-mean square difference were compared using paired t -tests for each intervention separately (alpha <0.05). Findings: Botulinum toxin induced significant changes in the joint angles, but did not improve the muscle and joint contact forces. Single-event multilevel surgery induced significant kinematic and kinetic changes, which were associated with improved muscle and joint contact forces. Interpretation: The present results indicate that botulinum toxin injections were not able to restore normal gait kinematics nor musculoskeletal loading, whereas single-event multilevel surgery did successfully restore both. Therefore, single-event multilevel surgery might be protective against the re-occurrence of bone deformation on the longer term. Highlights: Lower-limb joint loading during gait is aberrant in cerebral palsy patients. Single-event multilevel surgery restores lower-limb musculoskeletal loading Botulinum toxin injections do not improve lower-limb musculoskeletal loading